Drugs as environmentally benign corrosion inhibitors for ferrous and nonferrous materials in acid environment: An overview - Verma C.; Chauhan D.S.; Quraishi M.A. (My University, 2025)
Due to the increasing ecological awareness and environmental regulations, recent advancements in the field of corrosion science and technology is directed towards "green chemistry". One of the major factors that restrict the utilization of synthetic corrosion inhibitors is their toxic nature. The preparation of organic corrosion inhibitors is associated with the huge discharge of environmentally malignant chemicals into the surrounding environment. Commercially drugs present ideal candidature to replace these traditional toxic corrosion inhibitors. The article overviews the results of previous works describing the influence of chemical medicines on the corrosion inhibition of industrially important metals in acid solution. © 2017, University of Mohammed Premier Oujda Morocco.